A REVIEW ON SCHEMES FOR USER AUTHENTICATION - Ghorsad, Thamraj N; Pippal, Ravi Singh (IJRDO -Journal of Computer Science Engineering, 2015)
Textual-based password evidence scheme tends to be moreaccessible to attacks such as shoulder surfing and hiddencamera, eves dropping, dictionary attacks, socialengineering. To overcome the vulnerabilities of traditionalmethods, graphical password schemes have been developedas possible alternative solutions to text-based passwordschemes. Most of the graphical schemes are accessible toshoulder surfing. To solve this problem, text can becombined with images to generate session passwords forevidence. Session passwords can be used only once andevery time a new password is generated. In this paper, weintroduce a new evidence techniques “authentic recallbased”and Complect recall-based techniques